The physical mind debate - Oviedo, Lluis; Rasmussen, Steen (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
STEEN RASMUSSEN: I was looking so much forward to participate in this debate. I don’tremember when I have been in a forum where somebody was saying, I mean, was talkingabout God in this way, this is wonderful [...]